926. Outbreak of Invasive Nontuberculous Mycobacterium (NTM) Infections Associated With a Pediatric Dental Practice. (26th November 2018) - Singh, Jasjit; O'Donnell, Kathleen; Ashouri, Negar; Adler-Shohet, Felice C; Nieves, Delma; Tran, M Tuan; Arrieta, Antonio; Tran, Lisa; Cheung, Michele; Zahn, Matthew
Abstract: Background: In 2016, an Orange County, California, pediatric dental clinic's contaminated water system led to the largest outbreak of odontogenic NTM infections yet described. Methods: Mandatory reporting and active case finding directed by County Public Health were conducted in collaboration with community Pediatric Infectious Disease physicians for patients who underwent pulpotomy at Dental Clinic A from January 1 to September 6, 2016. Confirmed cases were those with positive NTM culture. Probable cases were those with multiple pulmonary nodules on computed tomography (CT), necrotic bone or osteomyelitis seen at surgery, or pathology with positive acid-fast bacilli stain, granulomatous inflammation or chronic osteomyelitis. Clinical data was collected from medical records. Results: Of 1, 089 patients at risk, 71 cases (22 (31%) confirmed and 49 (69%) probable) (Figure 1) had been identified as of March 19, 2018 (Figure 2). Median case age was 6 years (range 2–11 years). Symptoms began a median of 85 days (range 1–409 days) after pulpotomy (Figure 3). Pain and/or swelling on admission were reported in 79%; 21% were asymptomatic. CT findings included 49/70 with abnormalities of the mandible or maxilla, 13/70 with lymphadenopathy, and 19/68 with pulmonary nodules. Only 6/60 had erythrocyte sedimentation rate >40 mm/hour. Of 71 cases, 70 were hospitalized and underwent surgical debridement, for an average of 8.5 inpatient days (range 1–60 days); 23 had >1 hospitalization and 26 required >1 inpatient surgery. Permanent teeth were lost in 45/65 (range of 1–6 teeth lost). Intravenous antibiotics were administered to 32 cases for a median length of 137 days (range 113–282 days). Clofazimine was obtained for 29/32 cases as part of the regimen. Medical therapy was complicated by peripherally inserted central catheter malfunction/replacement/infection (18/27), rash (2/27), neutropenia (12/27), and elevated creatinine (7/27). All treated children showed evidence of jaw healing with resolved or improving lung nodules at 1-year follow-up. Conclusion: This is the largest outbreak of invasive NTM infections seen associated with a pediatric dental practice. While infections were indolent, patients suffered medical and surgical consequences of treatment. Enhanced national dental water quality standards are needed to prevent future outbreaks. Disclosures: A. Arrieta, Melinta Therapeutics: Investigator, Research support